2020
DOI: 10.1016/j.eclinm.2020.100344
|View full text |Cite
|
Sign up to set email alerts
|

HIGH-FREQUENCY failure of combination antiretroviral therapy in paediatric HIV infection is associated with unmet maternal needs causing maternal NON-ADHERENCE

Abstract: Background: Early combination antiretroviral therapy (cART) reduces the size of the viral reservoir in paediatric and adult HIV infection. Very early-treated children may have higher cure/remission potential. Methods: In an observational study of 151 in utero (IU)-infected infants in KwaZulu-Natal, South Africa, whose treatment adhered strictly to national guidelines, 76 infants diagnosed via point-of-care (PoC) testing initiated cART at a median of 26 h (IQR 18À38) and 75 infants diagnosed via standard-of-car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 28 publications
5
34
1
Order By: Relevance
“…As stated above, suppression of viraemia on ART is strongly correlated within mother-child pairs (Fig. 3I, j), because of shared ART non-adherence rather than shared ART resistance 25 . Comparing male infants and mothers of males with female infants and mothers of females, viral suppression is correlated within pairs (Supplementary Fig.…”
Section: Preferential Transmission Of Ifn-i-resistant Viruses To Femasupporting
confidence: 57%
“…As stated above, suppression of viraemia on ART is strongly correlated within mother-child pairs (Fig. 3I, j), because of shared ART non-adherence rather than shared ART resistance 25 . Comparing male infants and mothers of males with female infants and mothers of females, viral suppression is correlated within pairs (Supplementary Fig.…”
Section: Preferential Transmission Of Ifn-i-resistant Viruses To Femasupporting
confidence: 57%
“…It is also possible that infants born to mothers who did not receive ART may have had other host factors (HIV-specific immunity or genetic factors) that led to better viral control [ 29 , 30 ]. A similar finding was reported in a study of intrauterine-infected infants in KwaZulu-Natal, South Africa, where a longer duration of maternal ART during pregnancy was found to predict infant viral rebound [ 23 ]. Further data, particularly on maternal and infant drug resistance, are needed to disentangle and better understand these pathways.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, similar to the Botswana study, we did not observe any association between gestational age and viral response. In contrast, a study of intrauterine-infected infants in KwaZulu-Natal, South Africa found that infants born at a younger gestational age had lower rates of viral rebound [ 23 ]. For breastfeeding, we found a signal that breastfeeding may be associated with better viral response to early ART.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, in 2018, worldwide, approximately 160,000 infants were infected with HIV [ 2 ]. The currently available ART-based measures to prevent MTCT in WLWH are limited by implementation challenges, such as suboptimal ART coverage of pregnant and breastfeeding women [ 3 ], poor adherence to ART [ 4 , 5 ] resulting in incomplete viral suppression and increased risk of drug resistance, and late presentation for prenatal care [ 6 ]. In addition, ART-based prophylactic strategies do not address the scenario of acute maternal infections that occur late during pregnancy or during the breastfeeding period [ 7 ].…”
Section: Need For An Earlylife Hiv Vaccinementioning
confidence: 99%